Upaya Meningkatkan Aktivitas dan Hasil Belajar Matematika Pokok Bahasan Trigonometri dengan Menggunakan Model Pembelajaran Kooperatif Tipe NHT Siswa Kelas XII IPA 4 SMAN 3 Kotabumi Tahun Pelajaran 2018—2019 - Ana Riyana (Eksponen, 2019)
The main problem faced at SMA Negeri 3 Kotabumi is the low activity and student learning outcomes due to less varied learning methods. Therefore, this study aims to improve the activities and learning outcomes of Mathematics using NHT type cooperative learning models on Trigonometry material for SMA Negeri 3 Kotabumi students. This research was conducted to 34 students of class XII Science 4, in this study tested the use of NHT type cooperative learning models on Trigonometry material to determine their effects on student learning outcomes. The study was divided into 3 cycles by collecting data using cognitive tests and student attitude questionnaires obtained from each cycle, the results were analyzed whether there was an increase in each cycle. The results of this study indicate that there is an increase in learning outcomes 20% from cycle I to cycle II and an increase of 27% from cycle II to cycle III, while student activity has increased from cycle I by 78, to 81 in cycle II and 83 in cycle III, activity asessment indicators in the form of discipline, cooperation, courtesy and tolerance in learning